Digital supply chain management ecosystem powered by Blockchain Technology - Ahsan, Syed Rifat; Mehrin, Yousra; Yousuf, Ismat Sifat; Khan, Zunaira (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.